SYNTHESIS AND CHARACTERIZATION OF BIMEVOX (ME = CU, TI) AS SOLID ELECTROLYTE MATERIALS FOR SOFC - Deliana Dewi S, Citra
Bismuth vanadate polycrystals oxide, BiMeVOx (Bi2MexV1-xO5 ,5-?) with a metal dopant Me = Cu and Ti, have been synthesized by solid state reaction method at 850 0C for 48 hours. BiMeVOx single phase obtained with Ti metal insertion, but the crystal growth does not occur in Cu metal insertion. Crystal’s unit cell volume and pore surface concentration decreases with the increasing of Ti metal concentration, while the ionic conductivity increased significantly from 1.37 x10-4 S.cm-1 to 6.12 x10-3 S.cm-1 at 713 K. The temperature of BiMeVOx’s phase transition from ? phase into the ? phase, which known has a highest conductivity, decreases with the increasing of Ti metal concentration from 744 K at Ti concentration of x = 0.05 to 663 K at Ti concentration of x = 0.2. The relatively high ionic conductivity of BiMeVOx (Me = Ti) indicates that this material could be a potential electrolyte material in IT-SOFCs application.